(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Reflective abstraction can provide an insight into students’ understanding of mathematical concepts. The purpose of this qualitative research was to identify students’ understanding of derivative based on their reflective abstraction in solving graphically-represented question. Students’ understanding of derivative was evaluated by their ability in solving assignment concerning derivative and interview results. Results suggested that students use algebraic strategy to solvegraphically-represented question. Based on reflective abstraction, students constructed their knowledge through interiorization, reversal, coordination, encapsulation, and generalization. Difficulties that the students faced in solving graphically-represented question reflected from their answer and interview results are discussed.